Shlemiel crooks - Olswanger, Anna, 1953-; Goodman Koz, Paula (Montgomery, AL : Junebug Books, 2005)
Two crooks, following the inspiration of Pharaoh's ghost, fail to steal a precious shipment of kosher wine from Israel and lose their horse and wagon in the process.
Based on a true incident in the lives of the author's great-grandparents.
Bulletin (Center for Children's books).
School Library Journal.
6.2
3-6
Keywords: Jews -- United States -- History -- 20th century -- Juvenile fiction; Thieves -- Juvenile fiction; Historical fiction; Humorous stories; Jews -- United States -- History -- 20th century -- Fiction; Robbers and outlaws -- Fiction; Historical fiction; Humorous fiction; Jews -- United States -- History -- Fiction; Thieves -- Fiction; Saint Louis (Mo.) -- History -- 20th century -- Juvenile fiction; Saint Louis (Mo.) -- History -- 20th century -- Fiction; Saint Louis (Mo.) -- History -- Fiction; Historical fiction; Humorous fiction